(untitled) (Research, Society and Development, 2021)
The commercialization of natural products is an important cultural practice because, through this practice, the use of medicinal plants is widespread. The use of plants for therapeutic purposes requires the acquisition of raw materials correctly identified and prepared with quality criteria so that they can be used safely by the population. Common problems associated with the consumption of raw materials of plant origin are associated with the lack of quality control and the presence of adulterants. Considering the importance of the trade in plant drugs for the population and the risks that materials unsuitable for use may pose risks to human health, the present study set out to investigate the quality of raw materials of Curcuma longa (turmeric) and Coffea sp. (coffee), as well as the identification and presence of adulterants in samples sold in the supply centers of Goiânia-Goiás. The samples were obtained commercially at random from fairs and supply centers. Twenty samples of C. longa and 14 of Coffea sp. In the evaluation of quality parameters, the raw materials were adequate in terms of moisture and volatile content, as well as in the presence of ash. However, research on foreign material revealed that more than 50% of the samples had foreign materials used as adulterants, usually to increase the weight of the material. According to the results obtained, there were flaws in the process of commercializing coffee and saffron, since foreign matter was identified in samples taken from both species, in order to demonstrate that the lack of inspection can be harmful to consumers and economically.